Fetal and maternal responses to yoga in the third trimester. (2nd August 2020) - Gavin, Nicole R.; Kogutt, Benjamin K.; Fletcher, William; Szymanski, Linda M.
Abstract: Objective : The primary purpose of this study was to examine maternal and fetal responses to a typical, moderate-intensity yoga session in healthy pregnant women during the third trimester using continuous monitoring. Methods : This prospective observational study in low-risk, pregnant women used the Monica AN24 Abdominal ECG wireless maternal-fetal monitor to measure fetal heart rate, maternal heart rate, and uterine activity during a prenatal yoga session. Sessions included 4 time periods: (1) 20-minute rest, (2) 50 minutes standard prenatal yoga, (3) 10-minute meditation, (4) 20-minute recovery. Data were continuously recorded throughout the entire session, stored at 0.25-second intervals, and then averaged over 5-minute intervals. To evaluate changes over time, overall means for the four time periods (rest, yoga, meditation, recovery) were compared using one-way ANOVA with repeated measures. P ost -hoc pairwise comparisons (Tukey's) were used to probe significant differences between the four time points. Statistical significance was reached at p  < .05. Results : Twenty participants were enrolled; 19 completed the yoga session. Mean gestational age was 35 weeks and 6 days (range of 32–0/7 to 38–6/7) with an average participant age of 32 ± 2.7 years. Maternal heart rates significantly increased during the yoga period (102 ± 11 bpm) compared to rest (90 ± 10), meditation (85 ± 12), and recovery (88 ± 10) ( p  < .01). The maximum maternal heart rate reached during the yoga session was 125 ± 13 bpm. While fetal heart rates fluctuated slightly over the course of the yoga session, there were no significant fetal heart rate decelerations to suggest deleterious fetal effects. There were no statistically significant differences among resting (138 ± 14 bpm), yoga (137 ± 11 bpm), meditation (139 ± 7 bpm), or recovery (135 ± 22 bpm) fetal heart rates ( p  = .814). Uterine activity was significantly greater during the yoga period compared with the other time points ( p  < .001). Conclusion : Yoga can be recommended for low-risk women during pregnancy as no adverse fetal or maternal heart rate changes were observed during a typical prenatal yoga session.